Direito ao trabalho: reflexões sobre as pessoas com deficiência e sua (in)exclusão na administração pública - Mendes, Sandro Moretti Simão do Nascimento (Universidade Federal Rural do Semi-Árido, 2018)
The disabled persons is still experiencing a marked exclusion process with regard to access to their basic rights, especially with regard to work. What is more strange is that this state-of-things is not caused by the absence of legislation, but by a misinterpretation of it. In other words, what would be the solution is itself (to some extent) the cause of exclusion. We will demonstrate here how this ineffective inclusion of disabled persons in the public service framework is carried out, in the light of positive legal texts, corroborated by both the Public Administration (at its discretion) and by the High Courts' understanding (when interpreting the concrete case with elements of outside positive law). To do so, some original ideas will be defended, such as an increased percentage of vacancies, with a direct view of Public Administration personnel, whether or not they are permanent positions, as well as the reservation of permanent positions in the bidding documents. At the end of the analysis of our contemporary factual reality, we will arrive at a conclusion that removes any and all discriminatory interpretation given to date.
Monografia
Keywords: Pessoas com deficiência; Cargo público; Interpretação; Norma jurídica; Igualdade; CIENCIAS SOCIAIS APLICADAS::DIREITO